Pengaruh Bahasa Iklan Media Sosial Terhadap Peningkatan Penjualan Di Kota Padang - Saunir, Ihsan; Amril, Khairalfi Jumanisa; Amir, Amril (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2025)
This study aims to determine the influence of social media advertising language on sales improvement at Optik Jaya and Dian Optikal in Padang City. The background of this research is based on the phenomenon that many optical business owners have utilized social media as a promotional tool, but have not yet optimized the use of persuasive and emotional advertising language. This research uses a quantitative method with a survey approach. The sample consists of 100 respondents who are customers or social media followers of the two optical stores. Data were collected using a closed-ended questionnaire with a Likert scale and analyzed using simple linear regression. The results show that social media advertising language has a significant influence on sales improvement, with an R² value of 0.534. This means that 53.4% of the variation in sales increase is influenced by advertising language, while the remaining 46.6% is influenced by other factors. The findings indicate that using advertising language that is attractive, emotional, and culturally relevant can increase consumer interest and buying actions.